Book Review: Atas Nama Kebencian: Kajian Kasus-kasus Kejahatan Berbasis Kebencian di Indonesia: Penulis: Maruli C.C. Simanjuntak - Kartodiono, Sumarno (Jurnal Keamanan Nasional, 2018)
Indonesia in the last few years has been faced with religious-based intra-religious or inter-religious conflicts. What factors can lead to religious sentiment and trigger conflicts in Indonesia are the lighters of discussion in this book. In this book, Maruli CC Simanjuntak shows that utterances of hatred based on religion are one of the triggers for the birth of conflicts in Indonesia. Speeches of hatred have alienated minority groups and endangered their position.